Total engineering quality management - Sharma Sunil (Delhi Macmillan India, 2003)
The book deals in a distinctive manner, the management as well as engineering aaspects of planning , designing, controlling and improving quality in manufactured products. It deals with interface of Total Quality with a wide spectrum of activities rangin
Keywords: Total quality management